2009
DOI: 10.1094/mpmi-22-12-1555
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Ethylene and Jasmonic Acid Signaling Pathways in the Expression of Maize Defense Protein Mir1-CP

Abstract: In plants, ethylene and jasmonate control the defense responses to multiple stressors, including insect predation. Among the defense proteins known to be regulated by ethylene is maize insect resistance 1-cysteine protease (Mir1-CP). This protein is constitutively expressed in the insect-resistant maize (Zea mays) genotype Mp708; however, its abundance significantly increases during fall armyworm (Spodoptera frugiperda) herbivory. Within 1 h of herbivory by fall armyworm, Mir1-CP accumulates at the feeding sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 68 publications
2
43
2
1
Order By: Relevance
“…Plants that were treated with buffer or water to dissolve MCP and ETP, respectively, were used as the controls. These results are different from those with caterpillar infestation, where both JA and ET are indispensable for mir1 transcript and Mir1-CP protein accumulation (Harfouche et al, 2006;Ankala et al, 2009). Taken together, no-choice bioassays in conjunction with qRT-PCR analysis of mir1 transcript expression indicate that CLA feeding-induced expression of mir1 is independent of JA but dependent on the ET pathway.…”
Section: Rmir1-cp Provides Direct Toxicity To Clacontrasting
confidence: 57%
See 2 more Smart Citations
“…Plants that were treated with buffer or water to dissolve MCP and ETP, respectively, were used as the controls. These results are different from those with caterpillar infestation, where both JA and ET are indispensable for mir1 transcript and Mir1-CP protein accumulation (Harfouche et al, 2006;Ankala et al, 2009). Taken together, no-choice bioassays in conjunction with qRT-PCR analysis of mir1 transcript expression indicate that CLA feeding-induced expression of mir1 is independent of JA but dependent on the ET pathway.…”
Section: Rmir1-cp Provides Direct Toxicity To Clacontrasting
confidence: 57%
“…Previous studies with fall armyworm indicated that JA functions upstream of ET in the Mir1-CP pathway, but both are required for Mir1-CP accumulation in response to caterpillar feeding (Harfouche et al, 2006;Ankala et al, 2009). To further determine the role of ET in contributing to mir1-mediated defense against CLA, Mp708 plants were pretreated with 1-methylcyclopropane (MCP; commercially available as Ethylbloc) and ethephon (ETP), which block and activate the ET pathway, respectively.…”
Section: Rmir1-cp Provides Direct Toxicity To Clamentioning
confidence: 99%
See 1 more Smart Citation
“…This selection included the entire gene families of maize LOX (see Supplemental Table 1 online), OPR (Zhang et al, 2005), and JAZ genes (maize JAZs, see Supplemental Table 1 online; Arabidopsis JAZs, Yan et al, 2007). We also selected other defense genes of interest, including MPI (Tamayo et al, 2000), the ethylene biosynthesis genes ACS2, ACS6, and ACS7 (Young et al, 2004), the insect defense gene Mir1 (Ankala et al, 2009), the defensin gene PDC (Kant et al, 2009), and the anthocyanin biosynthesis genes A1, A2, C2, BZ1, and BZ2 (see Supplemental Table 1 online). The macroarray profile revealed that 67 of this 85-gene set, including LOX7/8, LOX9, AOS1, OPR7/8, MYC2, JAZ7, JAZ8, and MYC2, etc., were upregulated 1 and 2 h Table 1 online) in response to wounding of opr7-5 opr8-2 and wild-type plants.…”
Section: Opr7 Opr8 Mutants Are Compromised In Resistance To a Chewingmentioning
confidence: 99%
“…Although JA-regulated defense pathways have been extensively studied in the model plant Arabidopsis and other dicots (Howe and Jander, 2008), far less is known about their role in regulating direct herbivore defenses in monocots, especially in an economically significant crop like maize (Ankala et al, 2009). The creation of JA-deficient opr7 opr8 mutants provided an excellent tool to test whether JA has a similar insect defense signaling role in maize.…”
Section: Ja Is An Indispensable Signal In Maize For Defense Response mentioning
confidence: 99%